Answer:
y = -2x -5
Step-by-step explanation:
y - y1 = m (x - x1)
y + 1 = -2 (x + 2)
y + 1 = -2x -4
y = -2x -5
Hope this was helpful :)
B) $91,647
C) $243.64
D) $473.34
12x + 15
-12x + 15
Simplify: -5x + 8 - 11x - 12
-16x - 4
16x + 4
16x - 4
2(4x - 8) - 10
8x + 26
8x - 26
-8x - 26
Answer:
Step-by-step explanation:
2(4x - 8) - 10
8x-16- 10
|_______|
8x - 26
-5x + 8 - 11x - 12
_______________
_______
-16x - 4
-3(4x - 5)
-12x+15
For the third and first exercises, you just use the DistributiveProperty,and for the second exercise, all you are doing is combining like-terms.
I am joyous to assist you anytime.